2015
DOI: 10.1002/ece3.1453
|View full text |Cite
|
Sign up to set email alerts
|

Dispersive Raman spectroscopy allows the identification and quantification of melanin types

Abstract: Melanins are the most prevalent pigments in animals and are involved in visual communication by producing colored traits that often evolve as intraspecific signals of quality. Identifying and quantifying melanins are therefore essential to understand the function and evolution of melanin-based signals. However, the analysis of melanins is difficult due to their insolubility and the lack of simple methods that allow the identification of their chemical forms. We recently proposed the use of Raman spectroscopy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 17 publications
0
35
0
Order By: Relevance
“…Pheomelanin shows a distinctive Raman spectrum comprising three diagnostic bands located at 500, 1,500 and 2,000 cm −1 , and eumelanin shows different spectra with other diagnostic bands (Galván & Jorge, ; Galván et al, ; Polidori, Jorge, & Ornosa, ; Wang et al, ). In the flank feathers of male zebra finches, we only detected Raman signal from pheomelanin together with bands that can be assigned to keratin (Hsu, Moore, & Krimm, ).…”
Section: Methodsmentioning
confidence: 99%
“…Pheomelanin shows a distinctive Raman spectrum comprising three diagnostic bands located at 500, 1,500 and 2,000 cm −1 , and eumelanin shows different spectra with other diagnostic bands (Galván & Jorge, ; Galván et al, ; Polidori, Jorge, & Ornosa, ; Wang et al, ). In the flank feathers of male zebra finches, we only detected Raman signal from pheomelanin together with bands that can be assigned to keratin (Hsu, Moore, & Krimm, ).…”
Section: Methodsmentioning
confidence: 99%
“…The flank feathers of 16 nuthatch nestlings from 2017 were analyzed by micro-Raman spectroscopy to determine their relative content of melanins, as both pheomelanin and the non-sulphurated form of melanin (eumelanin) exhibit distinctive Raman signal that can be used to non-invasively identify and quantify them Jorge 2015). We used a Thermo Fisher DXR confocal dispersive Raman microscope (Thermo Fisher Scientific, Madison, WI, USA) with a point-and-shoot Raman capability of 1 µm spatial resolution and using a NIR excitation laser of 780 nm.…”
Section: Analysis Of Feather Pheomelanin Contentmentioning
confidence: 99%
“…used Raman spectroscopy as a non‐invasive technique for distinguishing eumelanin and pheomelanin pigments in the samples of partridge feathers, human and wild boar hairs. Recently, Galvan and Jorge characterized melanin pigments in bird feathers and reported that best results were achieved with the 785‐nm wavelength while keeping the laser power under 2 mW to avoid fluorescence disturbances. The pigments derived from sepia ink were historically used as the black colour pigments, and Raman spectroscopy was used to analyse melanin pigments in works of art .…”
Section: Introductionmentioning
confidence: 99%